Is metabolically healthy obesity indeed healthy at the microvascular level?. (25th November 2020) - Tibirica, E; Huguenin, G; Rodrigues-Junior, L; Pecanha, D; Duque, M; Escobar, S; Duque, A; Araujo, C; Mediano, M; Lorenzo, A
Abstract: Background: In the current "obesity epidemic", obese individuals without insulin resistance, lipid disorders, or hypertension, have been called "metabolically healthy" (MHO) and considered to have intermediate cardiovascular risk, between that of healthy nonobese (HNO) individuals and of metabolically unhealthy obese (MUO). Nonetheless, this is controversial, as MHO may have subclinical abnormalities, and indeed may be a transitory state in the way to the unhealthy phenotype. Purpose: To evaluate systemic microvascular reactivity in MHO, MUO and HNO. Methods: Ten MHO, 10 MUO and 20 HNO individuals were studied. Obesity was considered as a BMI ≥30 kg/m 2 . The NCEP/ATPIII criteria, excluding waist circumference, were used to define the metabolically healthy phenotype (absence of all criteria) or unhealthy phenotype (presence of any of the criteria). Laser speckle contrast imaging coupled with skin acetylcholine (Ach) iontophoresis was employed to study cutaneous microvascular reactivity (endothelial-dependent vasodilatation), as a surrogate for systemic microvascular function, and cutaneous vascular conductance [CVC in arbitrary perfusion units of microvascular flow (APU)/mean arterial pressure (mmHg)] was measured. Results: Mean age was 34.8, 36.7 and 32.3 years (P=0.17, ANOVA) and BMI was 20.7, 32.2 and 33.3 kg/m 2 (P<0.0001) for HNO, MHO and MUO, respectively. Both MHO and MUO had significantly decreased microvascular vasodilation in comparison to HNO (Figure 1). Of note, there was no significant difference between MHO and MUO regarding CVC (both similarly decreased when compared to the healthy controls). Conclusions: This study underscores that MHO is not a "benign" condition, as it has adverse effects on microvascular function, similarly to those found in MUO. The study of cutaneous microvascular function may be useful to identify subclinical abnormalities in obese individuals who might deserve more intensive management. Funding Acknowledgement: Type of funding source: Public Institution(s). Main funding source(s): FAPERJ - Fundação de Amparo à Pesquisa do Estado do Rio de Janeiro - Brazil